1790 Longitudinal coagulation profiles in patients presenting with acute severe traumatic brain injury (TBI): A prospective observational study. Issue 12 (22nd November 2022) - Barrett, Liam; Manktelow, Anne; Thomas, William; Disegna, Arthur; Needham, Ed; O'Leary, Ronan; Boyle, Adrian; Curry, Nicola; Stanworth, Simon; Newcombe, Virginia
Abstract : Aims, Objectives and Background: Patients who have sustained a traumatic brain injury (TBI) can have disturbances in coagulation that are distinct from other traumatic bleeding states.1 Coagulopathy is a risk factor for exacerbation of the primary injury, and these patients have less favourable outcomes and increased mortality compared to non-coagulopathic patients.1 Little is known about the longitudinal coagulation changes following TBI. The aim of this pilot study was to investigate the coagulation profiles of patients presenting with severe TBI over the first 7 days following injury. Method and Design: Design: Prospective observational study 25 patients presenting to an UK major trauma centre with TBI between August 2021-March 2022 were recruited <24 hours following injury. Professional and family consultee assent was gained and serial blood samples were collected up to three times per day up to day seven. Coagulation was assessed using thromboelastographs (TEGs) and conventional coagulation tests including Hb, Plt, PT, aPPT and fibrinogen. Pre-hospital, clinical, laboratory and imaging data were collected during the patient admission. Coagulopathy was defined as having an INR >1.2. The longitudinal changes in the coagulation parameters were plotted for the first seven 7 days and graphically represented. This is a pre-liminary analysis. Results and Conclusion: 25 patients with severe TBI (GCS <12) were recruited. Patients were stratified by their admission INR. 18 patients had an admission INR <1.2 (62% n= 18), and 7 had INR >1.2 (38% n=7). 7 patients who did not have INR >1.2 on their first admission blood test later developed coagulopathy (with an INR >1.2). Further exploration of the trends seen in conventional coagulation tests and TEG's over time is required and to understand how these changes correlate to the clinical and imaging findings. The utility of viscoelastic studies such as TEG's in the assessment of TBI associated coagulopathy remains unclear.